2019
DOI: 10.1103/physrevb.99.104109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cu intercalation and pressure on excitonic interaction in 1TTiSe2

Abstract: 1T-TiSe 2 has a semimetallic band structure at room temperature and undergoes phase transition to a triple-q charge density wave (CDW) state with a commensurate superlattice structure (2a × 2a × 2c) below T c ≈ 200 K at ambient pressure. This phase transition is caused by cooperative phenomena involving electron-phonon and electron-hole (excitonic) interactions, and cannot be described by a standard CDW framework. By Cu intercalation or the application of pressure, this phase transition temperature is suppress… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 77 publications
(130 reference statements)
3
21
0
1
Order By: Relevance
“…This indicates that the Ti 3d-Se 4p hybridization responsible for the ∼3 eV feature becomes stronger in the low-T CDW phase. This is consistent with the decrease in Ti-Se bond distances in the CDW phase, as is known from structural studies [38,60]. The T -dependent changes for the CW and CCW spectra are plotted as difference curves in the same figure.…”
Section: Resultssupporting
confidence: 86%
“…This indicates that the Ti 3d-Se 4p hybridization responsible for the ∼3 eV feature becomes stronger in the low-T CDW phase. This is consistent with the decrease in Ti-Se bond distances in the CDW phase, as is known from structural studies [38,60]. The T -dependent changes for the CW and CCW spectra are plotted as difference curves in the same figure.…”
Section: Resultssupporting
confidence: 86%
“…As for the Cu intercalation, T c becomes maximum of 3.79 − 4.15 K at x opt ≈ 0.077 − 0.08 in close proximity to the QCP of x c ≈ 0.06 − 0.07 at which the CDW is completely suppressed. [7,8] Also, Raman scattering experiments showed the frequency softening and divergent linewidth of the CDW amplitude mode corresponding to the L point as x approaches x c . [9,10] These seem in accord with the quantum critical superconductivity alluded above which suggests that the very interaction underlying the CDW formation may also induce the superconductivity in Cu x TiSe 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[11] As to the pressure, Kusmartseva et al observed by transport measurements that superconductivity appears in the range of P ≈ 2 − 4 GPa and the maximum T c ≈ 1.8 K occurs around P opt ≈ 3 GPa close to the CDW suppression. [12] However, Joe et al [13] and Kitou et al [14] observed with the synchrotron X-ray diffraction on single crystals that the P induced suppression is at P c ≈ 5.1 GPa which is more than 1 GPa beyond the end of the SC region. Joe et al also observed a reentrant incommensurate CDW phase appeared near the P opt above the SC dome which seemed to indicate that the pressure induced superconductivity in TiSe 2 may not be connected to the CDW suppression but to the CDW domain walls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notavelmente, o ZrTe 2 possui uma estrutura eletrônica praticamente idêntica ao TiSe 2 (ZUNGER; FREEMAN, 1978;FANG;GROOT;HAAS, 1997;BIANCO;CALANDRA;MAURI, 2015). O TiSe 2 é composto por hole-pockets Se-4p em Γ e electron-pockets Ti-3d situados no ponto de alta simetria L. Esse composto é amplamente estudado, sendo o sistema de estado sólido protótipo para o estudo da relação entre materiais de baixa dimensionalidade, transições de fase CDW (charge density waves) e supercondutividade (MOROSAN et al, 2006;KUSMARTSEVA et al, 2009;MOROSAN et al, 2010;ROHWER et al, 2011;MÖHR-VOROBEVA et al, 2011;LI et al, 2016;KITOU et al, 2019). Em T c = 202 K é possível observar uma anomalia na resistividade elétrica do TiSe 2 , caracterizando a transição do estado fundamental do sistema para uma fase CDW (SALVO; MONCTON;WASZCZAK, 1976).…”
Section: Estado Fundamental Do Zrteunclassified